A Legal Review of The Challenges and Opportunities on Strengthening The Role of The National Commission on Human Rights of The Republic of Indonesia - Chrisbiantoro Chrisbiantoro; Utami Yustihasana Untoro; Tarmudi Tarmudi (International Journal Labs, 2026)
This study examines the challenges and opportunities in strengthening the role of the National Commission on Human Rights of the Republic of Indonesia (Komnas HAM) in addressing gross human rights violations. The background of this research is rooted in the persistent delay in resolving human rights cases, largely due to institutional limitations, weak inter-agency coordination, and the lack of binding power in Komnas HAM recommendations, which ultimately undermines justice for victims. The objective of this research is to critically analyze these constraints while identifying strategic opportunities for institutional reform and improved legal mechanisms. This study employs a juridical-normative research method, utilizing statutory and conceptual approaches. Data were collected through library research, including primary legal materials such as Law No. 39 of 1999 and Law No. 26 of 2000, as well as secondary sources like academic literature and institutional reports. The data were analyzed using qualitative descriptive techniques, focusing on legal interpretation and institutional evaluation. The findings reveal that the primary issues lie in limited investigative authority, weak enforcement of recommendations, and coordination gaps between Komnas HAM and the Attorney General’s Office. The discussion highlights potential reforms, including expanding authority, strengthening reparations mechanisms, and enhancing cross-institutional collaboration. In conclusion, strengthening Komnas HAM requires comprehensive legal reform, clearer institutional authority, and improved coordination to ensure effective human rights enforcement and justice for victims